C-BANDING EVIDENCE FOR PERICENTRIC INVERSION POLYMORPHISM IN COMMON GREEN PIGEON TRERON PHOENICOPTERA PHOENICOPTERA (LATHAM) - N. GUPTA; D. KAUL (The Bioscan, 2012)
Forty eight birds of common green pigeon Treron phoenicoptera phoenicoptera (Latham) collected from different geographical areas like Allahabad (U.P), Chotanagpur and Singhbhum Divisions (Jharkhand) and Ganjam district (Odisha) have been subjected to C-banding analysis. The bird was found to be polymorphic for chromosome pairs 1 and 2. The polymorphism was explained on the basis of two independent pericentric inversions taking place in these chromosome pairs. With two chromosomes involved in inversions, ideally there should be nine types of karyomorphs. In the present investigation five different karyomorphs were encountered. All the karyomorphs were subjected to C-banding analysis. All the macrochromosomes have distinct C-bands at the centromere and three band sizes large, medium and small have been categorized purely on visual basis. Intercalary or terminal C- bands have not been observed in any of the macrochromosomes. No variant forms of C-bands have been recorded in the individuals examined during the present study. However, the shift in the position of C- band in the chromosome pairs 1 and 2 confirms that an inversion is responsible for the heterozygosity.